2009
DOI: 10.1111/j.1600-0854.2009.00948.x
|View full text |Cite
|
Sign up to set email alerts
|

Sorting of MHC Class II Molecules into Exosomes through a Ubiquitin‐Independent Pathway

Abstract: These authors contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 90 publications
1
57
0
Order By: Relevance
“…Furthermore, CD81 is important for the sorting of its associated proteins into exosomes [42]. Other studies support that the ubiquitination drives MHCIIcontaining MVBs to degradation upon fusion with the lysosomal system [52] (Fig. 1).…”
Section: Escrt-dependent and Independent Sorting Mechanisms Into Ilvsmentioning
confidence: 88%
See 1 more Smart Citation
“…Furthermore, CD81 is important for the sorting of its associated proteins into exosomes [42]. Other studies support that the ubiquitination drives MHCIIcontaining MVBs to degradation upon fusion with the lysosomal system [52] (Fig. 1).…”
Section: Escrt-dependent and Independent Sorting Mechanisms Into Ilvsmentioning
confidence: 88%
“…Depending on the added PTMs, these receptors can have different fates. Ubiquitinated-MHC-II is preferentially directed to degradative MVBs for degradation in lysosomes, whereas, Ub-LMP2A and ph-EGFR are usually incorporated into ILVs of exocytic MVBs, which are fused with plasma membrane to be secreted as EVs [52,77,116]. In the case of acetylated-GRP78 and ISGylated-TSG101, these PTMs act as cellular retention tags, promoting their degradation in lysosomes [128,129].…”
Section: Escrt-dependent and Independent Sorting Mechanisms Into Ilvsmentioning
confidence: 99%
“…This method has been reported to yield quantitative and reproducible results (22). Equal numbers of MJ and of MJ-gB cells were cultured in the same volume for the same time to produce exosomes.…”
Section: Release Of Gb-dr Complexes Via Exosomesmentioning
confidence: 99%
“…Although ubiquitination of the cytoplasmic region of HLA-DR (DR) regulates its subcellular trafficking, we and others have shown that it is dispensable for exosome entry (15)(16)(17)(18). Interestingly, the nonclassical MHC II molecule HLA-DM (DM) appears to be excluded from exosomes (19,20).…”
mentioning
confidence: 99%